2020
DOI: 10.1038/s41388-020-01562-y
|View full text |Cite
|
Sign up to set email alerts
|

FOXO3a-driven miRNA signatures suppresses VEGF-A/NRP1 signaling and breast cancer metastasis

Abstract: Metastasis remains the major obstacle to improved survival for breast cancer patients. Downregulation of FOXO3a transcription factor in breast cancer is causally associated with the development of metastasis through poorly understood mechanisms. Here, we report that FOXO3a is functionally related to the inhibition of VEGF-A/NRP1 signaling and to the consequent suppression of breast cancer metastasis. We show that FOXO3a directly induces miR-29b-2 and miR-338 expression. Ectopic expression of miR-29b-2/miR-338 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 47 publications
3
28
0
Order By: Relevance
“…VEGF-A can increase the permeability of and promote the formation of new blood vessels. 35 A recent study confirms that VEGF-A promotes Snail1 nuclear localization to drive the EMT by combining with the receptor in PCa. 36 VEGF-D plays a role in the formation of new blood vessels and lymphatic vessels in cancer tissue.…”
Section: Discussionmentioning
confidence: 85%
“…VEGF-A can increase the permeability of and promote the formation of new blood vessels. 35 A recent study confirms that VEGF-A promotes Snail1 nuclear localization to drive the EMT by combining with the receptor in PCa. 36 VEGF-D plays a role in the formation of new blood vessels and lymphatic vessels in cancer tissue.…”
Section: Discussionmentioning
confidence: 85%
“…Bioinformatic analysis using the Enhancer database revealed that the Snail promotor contains four consensus binding sites for FOXO3, raising the possibility that FOXO3 might directly regulate Snail expression through its ability to act as a transcriptional repressor. However, it has also been reported that FOXO3 can inhibit gene expression of Y-Box Binding protein-1 (YB-1), a protein that activates cap-independent translation of Snail mRNA [ 69 ], and/or induce mir-29, 30, and 34 transcription to reduce Snail mRNA levels [ 70 , 71 , 72 ], suggesting the potential for indirect post-transcriptional regulation. Therefore, the regulation of Snail expression by FOXO3 is complex, and further studies are required to determine the exact mechanisms involved in RA FLS.…”
Section: Discussionmentioning
confidence: 99%
“…Also, a miR-338-3p predicted target, VAPB, is recently suggested as a diagnostic biomarker in ALS that complicated in ER-associated aggregates [59]. More recently, Song et al reported FoxO3a induces miR-338-3p expression and may play a critical role in decreasing cell survival through directly suppressing the expression of NRP1 [60].…”
Section: Discussionmentioning
confidence: 99%